2011
DOI: 10.1021/ac202812h
|View full text |Cite
|
Sign up to set email alerts
|

Interferometric Methods for Label-Free Molecular Interaction Studies

Abstract: Figure 7. (A) BSI shows the difference in binding affinities for free-solution and surface-immobilized DNA hybridization. 25 (B) BSI detects the kinetic interaction of calmodulin and trifluoperazine. From ref 106. Reprinted with permission from American Association for the Advancement of Science, Copyright 2007. (C) Shows that the magnitude of binding as detected by BSI for α-crystallin to different T4L lysozyme mutants. Reprinted from ref 109.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
61
0
1

Year Published

2012
2012
2024
2024

Publication Types

Select...
4
2
2

Relationship

1
7

Authors

Journals

citations
Cited by 62 publications
(63 citation statements)
references
References 133 publications
(365 reference statements)
0
61
0
1
Order By: Relevance
“…Detection limits vary for SPR, but consistently reach ΔRI = 10 −6 . In our hands, the BSI detection limit is ΔRI = 10 −6 or 10-fold below this level (19,20,62). Therefore, using proper methodology the signal to noise ratio (S/N) of our interferometer should enable molecular interactions to be measured.…”
Section: Conformation and Hydration Changes Are The Origin Of Free-somentioning
confidence: 95%
See 2 more Smart Citations
“…Detection limits vary for SPR, but consistently reach ΔRI = 10 −6 . In our hands, the BSI detection limit is ΔRI = 10 −6 or 10-fold below this level (19,20,62). Therefore, using proper methodology the signal to noise ratio (S/N) of our interferometer should enable molecular interactions to be measured.…”
Section: Conformation and Hydration Changes Are The Origin Of Free-somentioning
confidence: 95%
“…The importance of these preliminary studies was not more fully realized until 2007, when our group showed that binding events, such as ion-protein, protein-protein, and small molecule-protein interactions, could be measured using a RI technique in free solution and without labels (9). Numerous examples have validated that free-solution measurements by interferometry can be used to quantity interactions of widely different affinities (micromolar to picomolar) and on interacting pairs with significant mass differences (>10,000-fold) (18)(19)(20). Although we, and others, have postulated the origin of the free-solution signal, no explicit explanation for the physical phenomenon has emerged.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Back-scattering interferometry (BSI) is an emerging technique for measuring molecular interactions in solution without the need for labeling or immobilization [80]. The platform consists of a collimated coherent light source (HeNe laser), a capillary or microfluidic chip containing the sample, and a CCD array detector.…”
Section: Back-scattering Interferometrymentioning
confidence: 99%
“…En una revisión más reciente [Kussrow, 2012] se analizan en particular los métodos interferométricos aplicados a la implementación de sistemas biosensores. Esta revisión, uno de cuyos autores es el autor de los primeros estudios de backscattering en capilares y canales rectangulares, es particularmente interesante por la revisión de los últimos logros de esta técnica en cuanto a sensibilidad y límite de detección.…”
Section: La Celdas Biofotónicas Bicellunclassified